The Interpretation of the Law in the Light of the Constitution. The So-Called "Conforming Interpretation" in the Relationship between the Corte Costituzionale and Ordinary Judges in Italy - Romboli, Roberto (2007)
In this paper, the author examines the relationship that has developed between the Italian Corte Costituzionale and ordinary judges with respect to the interpretation of the law in the light of the constitution in the fifty years of the functioning of constitutional justice in Italy. To this end, the first years of constitutional jurisprudence will be analyzed, with emphasis on the concept of "conforming interpretation", whose method seeks to give the law a meaning that avoids having to declare it unconstitutional; that is, it is intended to attribute to the law a meaning that is compatible with the Constitution. For this reason, the author analyzes how this concept originated, how it has evolved and how it is applied in the Italian judicial system, especially in relation to ordinary judges and the Corte Costituzionale.  Finally, it is intended to outline from this experience some general conclusions regarding the relationship between the Corte Costituzionale, which is the body in charge of controlling the constitutionality of laws, and the ordinary judges, who are the ones who apply the law in concrete cases in the model of constitutional justice.